PENGARUH MOTIVASI DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA DAN IMPLIKASINYA TERHADAP DISIPLIN KERJA TENAGA PARAMEDIS PADA RUMAH SAKIT UMUM DAERAH DR. R. M. PRATOMO KABUPATEN ROKAN HILIR - ', Ismail Jabar; ', B. Isyandi '; ', Susi Hendriani (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This study aims to analyze the influence of motivation and leadership on job satisfaction and its implications for labor discipline Medics On General Hospital Dr. R.M. Pratomo Rokan Hilir and partial simultaneously. The samples were whole paramedics at the Hospital Dr. R.M.Pratomo totaling 100 people. Data was collected through questionnaires using a Likert scale. The data obtained in this study was processed using SPSS (statiscal Program For Social Science) 19.0 for windows. These results indicate that in partial motivation no positive effect on job satisfaction paramedics, whereas the leadership variables have a significant influence on job satisfaction. While simultaneously motivation and leadership variables significant influence on job satisfaction paramedics. While the link between job satisfaction and discipline did not have a significant effect. It can be concluded that only partial variable that has pengauh leadership on job satisfaction while no motivation. Simultaneously both variables have an influence on job satisfaction influences job satisfaction, while there is no influence on the discipline. From these results it is expected that management leadership is expected to be a factor of concern in order to provide job satisfaction for employees, while the motivation despite having no effect, but the organization is expected to provide positive motivation for employees to be more employee satisfaction levels increased and in improving discipline in addition to creating job satisfaction then management needs to implement a system of monitoring and sanctions to discipline paramedics who are not in work. This solution can be expected to further improve the performance of the paramedics in Hospital Dr. R.M.Pratomo Rokan Hilir.Kata Kunci : Motivation, Leadership, Job Satisfaction and Work Discipline.